Analysis of tax incentive policies to encourage investment in the Nusantara Capital City (IKN) - Aditya, I Putu Bayu Krisna; Yunisti, Marcellina Evi; Briliana, Kharisma Dian Meta (Educoretax, 2025)
This study aims to analyze tax incentive policies that can encourage investment in the development of the Nusantara Capital City (IKN). This study employs a qualitative research method with a descriptive approach, utilizing secondary data gathered from a range of sources, including literature, documents, scientific journals, official government websites, and other reliable sources. The study's results indicate that the government provides various types of tax incentive policies to encourage investment in the development of the IKN. These various tax incentives have a positive impact on increasing investment in the IKN. However, this policy faces challenges due to the existence of global minimum tax provisions, as implemented through Pillar 2 of the Base Erosion and Profit Shifting (BEPS) 2.0 initiative. Additionally, tax incentives are not the primary factor that encourages investment. Therefore, the government can immediately formulate further regulations related to tax incentive policies by adjusting the provisions of Pillar 2 BEPS 2.0. For further researchers, it is advisable to develop more concrete and specific tax incentive policies in the IKN.